National Economic Resilience in The Face if Global Economic Crises: Macroeconomic Perspective - Akhyar, M; Rahmi, R. (Manunggal Halim Jaya, 2024)
This study aims to explore the concept of national economic resilience, specifically in the context of global economic crises, from a macroeconomic perspective. The primary objective is to examine the factors contributing to economic resilience, including fiscal and monetary policies, structural reforms, institutional quality, and international cooperation. This research utilizes a qualitative methodology, focusing on a systematic literature review of existing studies, academic articles, and policy reports related to economic resilience. The analysis of the literature allows for a comprehensive understanding of how nations absorb, adapt to, and recover from external shocks, with a particular focus on the role of macroeconomic policies and structural reforms in fostering resilience. The findings reveal that effective fiscal and monetary policies, alongside proactive structural reforms, are essential for enhancing economic resilience. Moreover, strong institutions and international cooperation are critical in supporting national economies during times of crisis. The study also highlights the importance of measuring resilience in a more comprehensive manner, integrating both short-term recovery and long-term adaptability. One of the key findings is that economies with strong institutional frameworks and flexible policies are better equipped to handle global shocks and recover more quickly. The research further suggests that developing countries face unique challenges and need tailored strategies to enhance their resilience. Overall, this study contributes to the growing body of knowledge on economic resilience, offering valuable insights for policymakers and researchers aiming to improve national economic stability in an increasingly interconnected global economy.